2007
DOI: 10.1615/critrevimmunol.v27.i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Modulatory Effects and Potential Working Mechanisms of Orally Applied Nondigestible Carbohydrates

Abstract: Orally applied nondigestible carbohydrates (NDC) have been associated with immune-modulating effects and other health benefits. The effects of prebiotic carbohydrates have recently received much attention, but other NDC have been reported to induce immune modulation as well. Many different effects have been shown on parameters of innate and specific immunity, mostly in animal experiments or in vitro. Data from clinical trials are limited, but promising studies have reported beneficial effects on mucosal and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(133 citation statements)
references
References 0 publications
3
122
0
5
Order By: Relevance
“…This may be related to a fermentation product of inulin, as it has been reported that butyrate suppresses lymphocyte proliferation, reduces cytokine expression and enhances IL-10 production in rats. However, as Peyer's patches are located in the small intestine, whereas fructans are fermented mainly in the large intestine, it could be speculated that microbiota-independent mechanisms may also have a role in the observed effects (Vos et al, 2007).…”
Section: Effects On Immune Parametersmentioning
confidence: 99%
“…This may be related to a fermentation product of inulin, as it has been reported that butyrate suppresses lymphocyte proliferation, reduces cytokine expression and enhances IL-10 production in rats. However, as Peyer's patches are located in the small intestine, whereas fructans are fermented mainly in the large intestine, it could be speculated that microbiota-independent mechanisms may also have a role in the observed effects (Vos et al, 2007).…”
Section: Effects On Immune Parametersmentioning
confidence: 99%
“…The optimal dose, formulation, relative contributions of EPA and DHA in fish oil and the target population remain yet to be defined (Fearon et al, 2006;Sijben and Calder, 2007). The use of non-digestible carbohydrates, especially of prebiotic oligosaccharides, is based on the immunemodulating activities observed in several animal experiments and clinical trials (Vos et al, 2007). In an influenza vaccination model in healthy C57BL/6 mice, a specific mixture of oligosaccharides stimulated the vaccine-specific delayed-type hypersensitivity response as a marker for T-helper 1 (Th1) immunity (Vos et al, 2006).…”
mentioning
confidence: 99%
“…Prebiotics are nondigestible dietary compounds that can be metabolized by specific microflora in the gut (Gibson and Roberfroid, 1995). Typical benefits include improved nutrient assimilation, growth and immune function (Vos et al, 2007). A dairy/yeast prebiotic had beneficial effects in golden shiners Notemigonus crysoleucas and goldfish Carassius auratus in our laboratory (Lochmann et al, 2009;Lochmann et al, 2011), but the same dairy/yeast prebiotic did not enhance growth or feed conversion of channel catfish at optimal temperatures (27°C to 28°C) (Thompson, 2009).…”
Section: Introductionmentioning
confidence: 93%